Pemanfaatan Aplikasi Mobile Assistant Untuk Mendeteksi Kerumunan dalam Penerapan New Normal Covid-19 - Nova Noor Kamala Sari; Widiatry Widiatry (Politeknik Caltex Riau, 2021)
The new normal life post COVID 19 pandemic can utilize the technology to support the implementation of social distancing, particularly in finding out the number of crowds or people gathering in an event or a location accurately. The process so far is done by manual counting which requires a lot of efforts. This information is demanded to suppress the number of COVID 19 cases. Therefore, the mobile application that can be used anywhere and can support high mobility is currently needed. This study tries to create a Mobile Assistant Application based on the Android Operating System, by incorporating a tracking function from the location using GPS (Global Positioning System) or a method commonly called Location Based Services (LBS) to inform the people’s presences in public places that can be accessed such as market, office, hospital, praying building, school and others. Software development method will apply the Extreme Programming method cosisting of four stages namely planning, design, coding and testing. This application can support the Government's performance in carrying out the new normal life and finding out the number of crowds, so that the social distancing can run optimally and reduce the virus spread.